Application of Big Data Technology in Financial Auditing: Challenges, Opportunities, and Implications for the Accounting Profession - Hendrawan, Henky; Suwandi Ng; Rusiana Sari, Agustin; Azizi, Muhammad; Verawaty (Dinasti Publisher, 2024)
The integration of Big Data technology in financial auditing has transformed traditional auditing practices, offering significant opportunities for enhancing audit quality and efficiency. This literature review examines the challenges, opportunities, and implications of Big Data technology in the accounting profession. It explores how Big Data tools and techniques can improve data analysis, risk assessment, and fraud detection. However, the adoption of Big Data also presents challenges, such as data privacy concerns, the need for specialized skills, and the complexity of managing large datasets. This review highlights the current state of research in this field and provides insights into the future directions for incorporating Big Data in financial auditing. The findings underscore the necessity for continuous professional development and the adaptation of regulatory frameworks to fully harness the benefits of Big Data technology